Seebeck’s effect in p-SiGe whisker samples - Dolgolenko, A.P.; Druzhinin, A.A.; Karpenko, A.Ya.; Nichkalo, S.I.; Ostrovsky, I.P.; Litovchenko, P.G.; Litovchenko, A.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
p-SiGe whisker samples with a diameter of ~40 μm, grown by chemical precipitation from the vapor phase, have been investigated. Temperature dependences of the thermal e.m.f. and conductivity within the temperature interval 20…400 K have been measured. It has been shown that the mobility of holes in p - SiGe whiskers upon the average is 1.5 times higher than that in bulk p - Si samples. p - SiGe whiskers possess smaller phonon scattering and larger phonon dragging in comparison with the bulk p - Si samples.